Spirulina supported plant growth in regolith simulants and elevated levels of CO2 - Miller, Kristen A.; Trevino, Dennis Terry; Cauthorn, Gilbert (Frontiers in Space Technologies, 2025)
IntroductionA key element for sustainable off-world habitation is the ability to grow food through in-situ resource utilization (ISRU). Growth substrates are required to overcome the challenges of ISRU in the space environment, including the use of regolith. Biofertilizers such as algae are a promising avenue for supporting plant growth with ISRU; algae can potentially mitigate the lack of nutrients, alkalinity, heavy-metal contamination, poor water-carrying capacity, and presence of perchlorates in regolith as well as increase plant growth at elevated levels of atmospheric CO2. The blue-green cyanobacterium Arthrospira platensis is an ionizing radiation resistant strain with high temperature tolerance and nutritional properties. It has been used successfully as a bio-fertilizer in heavy metal contaminated, highly alkaline terrestrial soilsMethodsOur research is a large-scale investigation of the efficacy of spirulina to enhance the growth of Raphanus sativus (Organic Daikon radish) microgreens using lunar and Martian regolith simulants. We present a study of growth for a wide range of regolith simulant-soil mixtures as a function of fertilizer concentration and the level of environmental CO2.ResultsSpirulina boosts growth for radish microgreens significantly; Martian regolith simulant with 0.6% spirulina under elevated CO2 yielded the best results. Water-only groups declined after the initial growth phase; spirulina fertilized groups maintained steady growth rates over the full growing period. Regolith simulant type influenced biomass more than height, with the best growth found in Martian rather than lunar regolith simulant. No difference was found between the different regolith simulant-to-soil mixtures.DiscussionThis research advances the application of ISRU to enhance self-sufficient, sustainable space exploration and resource use. In this research, spirulina fertilization compensated for the non-nutritive properties of regolith, supporting plant growth without the addition of terrestrial soils. This work suggests that spirulina can serve as an effective biofertilizer in soil farming practices using ISRU as a potential means of supporting off-world habitation.